Attitudes of the Members at the College of Basic Education towards Using Artificial Intelligence Applications in Scientific Research - Mohammed, Asst.Prof.Dr. Naznin Othman Mohammed (Sulaimani Journal for Humanities, 2025)
This study aims to investigate the attitudes of academic staff in the College of Basic Education towards using Artificial Intelligence (AI) applications in scientific research. It explores their attitudes across four dimensions of the scale: the benefits of using AI in scientific research, ethical concerns, future trends, and challenges and risks. The study also aims to reveal differences in attitudes based on the variables of gender (male-female), specialization (scientific-humanities), and years of experience. The researcher adopted the "Attitudes of Academic Staff towards Using AI Applications in Scientific Research" scale, developed by Sheikh Mohammed (2025). The scale consists of 44 items distributed across four domains. After establishing content validity and reliability using the Cronbach's Alpha method, the scale was administered to a sample of 72 individuals. The results indicate a moderate level of attitudes among academic staff in the College of Basic Education towards using AI applications in scientific research. The domains were ranked as follows: Ethical Concerns (First Place). Benefits of AI (Second Place).Challenges and Risks (Third Place).Future Trends (Fourth Place). Additionally, statistically significant differences were found in the sample's attitudes based on gender, favoring males. In contrast, no statistically significant differences were found based on the variables of specialization and years of experience. In light of these findings, the researcher provided a set of recommendations, most notably the need for Kurdistan Region universities to establish a comprehensive ethical charter for academic staff. This charter should include fundamental principles of academic integrity, as the uncontrolled use of AI, despite being a powerful tool to enhance research efficiency, could threaten scientific integrity and the originality of research.
Keywords: Artificial intelligence; trends; faculty members; scientific research; College of Basic Education